Electron-impact coherence parameters for 41P1 excitation of zinc. (4th April 2018) - Piwiński, Mariusz; Kłosowski, Łukasz; Chwirot, Stanisław; Fursa, Dmitry V; Bray, Igor; Das, Tapasi; Srivastava, Rajesh
Abstract: We present electron-impact coherence parameters (EICP) for electron-impact excitation of 4 1 P 1 state of zinc atoms for collision energies 40 eV and 60 eV. The experimental results are presented together with convergent close-coupling and relativistic distorted-wave approximation theoretical predictions. The results are compared and discussed with EICP data for collision energies 80 eV and 100 eV.